FUZZY HX FIELD - M.S. Muthuraman , M. Sridharan , K.H. Manikandan , G. Sabarinathan ,R. Muthuraj (International Journal of Modern Agriculture, 2021)
In this paper, we define the notion of fuzzy HX field of a HX field and some of their related properties are investigated. We introduce the concept of an image, pre-image, anti image and anti pre-image of an fuzzy subset and discuss in detail a series of homomorphic and anti homomorphic properties of an fuzzy set are discussed